STUDY ON SOME FACTORS ASSOCIATED WITH ECZEMA IN RAMADI. - Abdulla S. Hassan; Shehab A. Lafi; Zaynab K.Yousif (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Eighty eczematous patients were included in this study from both sexes and two age groups, adults were (52) patients aged (18-70) years and children were( 28) included aged (3-17) years. They were attending Department of Dermatology in Ramadi General Hospital Ramadi, Al-Anbar Governorate West of Iraq, during the period extended from April2005-March 2006. Patients were submitted to a clinical examination and questionnaire test. Data were analyzed using Chi - square and T test. Results showed that females within age group (3-17) years showed higher rate of eczema than males. Adult males showed higher of eczema , (18: 80 ) patients were showing familial link, adult females were more allergic to variety of food. Out of the total studied patients (61.25%) showed seasonal eczema while 38.75% of them showed eczema at any season